Structure activity relationships of αv integrin antagonists for pulmonary fibrosis by variation in aryl substituents - Adams, James; Anderson, Edward C.; Blackham, Emma E.; Chiu, Yin Wa Ryan; Clarke, Thomas; Eccles, Natasha; Gill, Luke A.; Haye, Joshua J.; Haywood, Harvey T.; Hoenig, Christian R.; Russell, Hannah L.; Smedley, Christopher; et al. (American Chemical Society, 2014)
Antagonism of alphav beta6 is emerging as a potential treatment of idiopathic pulmonary fibrosis based on strong target validation. Starting from an alphav beta3 antagonist lead and through simple variation in the nature and position of aryl substituent, the discovery of compounds with improved alphav beta6 activity is described. The compounds also have physicochemical properties commensurate with oral bioavailability and are high quality starting points for a drug discovery programme. Compounds 33S and 43E1 are pan alphav antagonists having ca 100 nM potency against alphav beta3, alphav beta5, alphav beta6 and alphav beta8 in cell adhesion assays. Detailed structure activity relationships with these integrins are described which also reveal substituents providing partial selectivity (defined as at least a 0.7 log difference in pIC50 values between the integrins in question) for alphav beta3 and alphav beta5.